Analisis Fundamental Makro, Fundamental Mikro Terhadap Nilai Perusahaan dengan Struktur Kepemilikan, Kinerja Keuangan dan Karakteristik Perusahaan Sebagai Variabel Intervening pada Perusahaan Sekor Makanan dan Minuman (F&B) yang Terdaftar pada Bursa Efek Indonesia pada Tahun 2018-2023 - Yunari, Syahna Shinta; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to determine and analyze the relationship between macro fundamentals and micro fundamentals on company value and intervening variables in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange during 2018-2023. The number of samples used in this research was 6 companies using a purposive sampling method. The data analysis technique in this research uses SMART-PLS software version 4. The test results show that the negative and insignificant influence is macro fundamentals on company value, micro fundamentals on company characteristics, ownership structure on company value and financial performance on company value. Meanwhile, those with a positive and insignificant effect are macro fundamentals on ownership structure, macro fundamentals on financial performance, micro fundamentals on company value, micro fundamentals on financial performance and company characteristics on financial performance. The variable that has a positive and significant effect is ownership structure on financial performance, apart from that the variable that has a negative and significant effect is company characteristics on company value.